Graphs
and
equations



A summary of everything that we now know which will help us to sketch curves of the form y = ax2 + bx + c 1. 2. 3. 4. If a is positive, the curve is U-shaped. If a is negative, the curve is an upside-down U. The value of c tells us the y-intercept. The curve crosses the y-axis at (0,c). We can factorize (or use the formula) to find whether and where the curve cuts the x-axis. If b2 – 4ac is negative, the curve does not cut the x-axis at all. We can complete the square to find where the least value of the curve is (or the greatest value, if it is an inverted U-shape). We shall see in Section 8.E.(b) that this can also be found by using calculus. If the curve does cut the x-axis, substituting the midway value of x between the cuts into the equation for y gives the least value of y (or the greatest value of y if the curve has an inverted Ushape).

Stretching and shifting – new functions from old (1) Adding a fixed amount to a function
What happens if we go from f (x) to f (x) + a, where a is some given constant number? Here are two examples, both taking a = 3. (a) f (x) = 2x + 1 (b) f (x) = x2 so f (x) + 3 = 2x + 4. so f (x) + 3 = x2 + 3. I show sketches of the two pairs of graphs below in Figure (a) and (b). 


We see that the effect of adding 3 to f (x), so that y = f (x) + 3, is to shift the graph up by 3 units.

(2) Adding a fixed amount to each x value
What will happen if we add a fixed amount to each x value instead, so that we go from f (x) to f (x + a) in each case? Again, we look at two examples, taking a = 3.

(a) f (x) = 2x + 1 (b) f (x) = x2

so f (x + 3) = 2(x + 3) + 1 = 2x + 7. so f (x + 3) = (x + 3)2.

Notice that, to find f (x + 3) from f (x), we just replace x by (x + 3). This time, the effect is to slide the whole graph 3 units to the left.

(3) Multiplying the original function by a fixed amount
What will happen if we go from f (x) to a f(x) where a is some given constant number? Working with the same two examples as before, and with a = 3 again, we get (a) f (x) = 2x + 1 (b) f (x) = x
2

so so

3f (x) = 6x + 3 3f (x) = 3x2

Sketches of the two pairs of graphs are shown below in Figure (a) and (b).

This time, the whole graph has been pulled away from the x-axis by a factor of 3, so that every point is now three times further away than it was originally. Therefore the only points on the graph, which will remain unchanged, are those on the x-axis itself.

(4)
Multiplying
x
by
a
fixed
amount

What will happen if we go from f (x) to f (ax)? Taking our same two examples, with a = 3, we have (a) f (x) = 2x + 1 (b) f (x) = x2 so so f (3x) = 2(3x) + 1 = 6x + 1 f (3x) = (3x)2 = 9x2.

Notice that we simply replace x by 3x to find f (3x) from f (x). I show sketches of the two pairs of graphs below in Figure (a) and (b). This time the stretching effect is more complicated because it only affects the part of the function involving x. Any purely number parts

remain unchanged. The points which are unaffected by the stretching are those where the graphs cut the y-axis, so x = 0. Notice too that the strength of the effect now depends upon the power of x. Having (3x)2 in example 4(b) gives a more extreme effect than the 3x2 in 3(b), since the 3 is also being squared here.

A
summary
of
some
effects
of
transforming
functions
 (1)
Transforming
f
(x)
to
f
(x)
+
a
shifts
the
whole
of
f
(x)
upwards
by
a
distance
a.
We
have
 


(2)
Transforming
f
(x)
into
f
(x
+
a)
shifts
the
whole
of
f
(x)
back
a
distance
a,
because
the
curve
is
getting
to
 each
of
its
values
faster,
by
an
amount
a.
We
have
fig.
(b)


 (3)
Transforming
f
(x)
into
af
(x)
stretches
out
each
value
of
f
(x)
by
a
factor
a.
We
have
fig.
(c)



 (4)
Transforming
f
(x)
into
f
(ax)
has
a
more
complicated
effect,
since
how
much
a
affects
each
part
of
f
(x)
 depends
on
what
is
happening
to
x
itself
in
f
(x).
For
example,
if
f
(x)
=
x2
+
x
+
1,
then
f
(ax)
=
a2x2
+
ax
+
1.
 Each
term
has
been
affected
differently.
Therefore
it
is
not
possible
to
show
this
case
on
one
sketch;
the
 change
in
shape
will
depend
entirely
upon
the
function
concerned.
 
 



 



 Even
functions


A
function
is
even
if
it
is
symmetrical
about
the
y‐axis.
For
these
functions,
f
(x)
=
f
(–x)
for
any
value
of
x.
 
 Odd
functions
 A
function
is
odd
if
rotation
through
a
half‐turn
leaves
it
unchanged.
This
is
the
same
as
saying
that
the
 function
reverses
its
sign
if
it
is
reflected
in
the
y‐axis,
so
f
(x)
=
–
f
(–x).
 



 See
if
you
can
decide
which
of
(a),
(b),
(c)
and
(d)
have
inverse
functions.
(a)
and
(c)
will
each
have
an
 inverse
function
because
each
value
of
y
is
given
by
only
one
possible
value
of
x,
but
(b)
and
(d)
will
only
 have
inverse
relations.
 With
(b)
for
example,
if
y
=
4
then
x
could
be
+2
or
–2.
 If
y
=
x2
then
x
=
y1/2.
The
inverse
relation
is
x
:
x1/2,
and
x1/2
can
be
either
+
or
–.
 The
sketch
in
Figure
(a)
shows
the
graphs
of
y
=
x2
and
its
inverse
relation
y
=
x1/2.
However,
if
we
say
that
x
 cannot
be
negative,
so
that
we
restrict
the
domain
of
y
=
x2
to
values
of
x
which
are
greater
than
or
equal
to
0
 (which
we
write
as
x
≥
0),
then
we
shall
have
a
perfectly
good
inverse
function
which
is
y
=
√x.
This
is
 shown
in
Figure
(b).
The
symbol
√is
taken
to
mean
the
positive
square
root
only.



 



 



 
 


Finding
and
working
with
the
equations
which
give
circles

How
can
we
find
the
equation
of
the
curve
which
gives
a
particular
circle
in
terms
of
x
and
y?

 We
will
start
by
considering
the
simplest
case
which
is
a
circle
of
radius
r
symmetrically
placed
so
that
its
 centre
is
at
the
origin.



 Any
point
P
on
it,
with
coordinates
(x,
y),
must
be
a
distance
r
from
the
origin,
so
x2
+
y2
=
r2
by
Pythagoras’
 Theorem.
The
equation
of
the
circle
with
centre
(a,b)
and
radius
r
is
given
by
(x
–
a)2
+
(y
–
b)2
=
r2.



 The
equation
of
the
circle
with
centre
(a,b)
and
radius
r
can
also
be
written
as
 x2
–
2ax
+
y2
–
2by
+
c
=
0
where
c
=
a2
+
b2
–
r2.
 
 For
an
equation
like
this
to
give
a
circle
it
must
fit
the
following
conditions.
 (1)
There
must
be
equal
coefficients
of
x2
and
y2.
The
coefficient
is
the
number
which
tells
us
how
many
 we’ve
got.
The
coefficient
of
3x2
is
3.
The
coefficient
of
y2
is
1.
If
there
are
no
terms
in
x,
say,
then
the
 coefficient
of
x
is
zero.
 (2)
There
must
only
be,
at
the
most,
terms
in
x2,
y2,
x,
y
and
a
number.
(We
mustn’t
have
any
terms
with
xy,


 for
instance.)
 (3)
The
value
of
r2
must
be
positive
so
that
we
have
a
physically
possible
length
for
the
radius.
 

Example
(1)
Find
whether,
and
if
so
where,
the
lines
(a)
y
=
2x
–
4
(b)
3y
=
x
+
11
and
(c)
y
=
3x
+
6
cut
the


circle
whose
equation
is
x2
–
4x
+
y2
–
2y
–
5
=
0.
Draw
a
sketch
showing
the
three
lines
and
the
circle.
 
 Answer:

(a)
If
the
line
y
=
2x
–
4
cuts
the
circle,
the
values
of
x
and
y
at
the
points
where
it
cuts
must
fit
both
 the
equations
of
the
circle
and
of
the
line.
 This
means
that
we
can
put
y
=
2x
–
4
into
the
equation
of
the
circle
to
find
the
possible
values
of
x.
 This
gives
us
 x2
–
4x
+
(2x
–
4)2
–
2(2x
–
4)
–
5
=
0
 x2
–
4x
+
4x2
–
16x
+
16
–
4x
+
8
–
5
=
0
 5x2
–
24x
+
19
=
0
 (5x
–
19)(x
–
1)
=
0
 x
=
1
or
x
=
19/5
.
 Substituting
these
values
of
x
back
in
the
line
y
=
2x
–
4
gives
us
the
corresponding
two
values
for
y
of
–2
and
 18/5.
So
the
line
y
=
2x
–
4
cuts
the
circle
at
the
two
points
with
coordinates
(1,
–2)
and
(19/5,18/5).
 (b)
To
find
if
the
line
3y
=
x
+
11
cuts
the
circle,
we
can
rewrite
its
equation
as
 x
=
3y
–
11
and
substitute
this
for
x
in
the
equation
of
the
circle.
This
gives
us
 (3y
–
11)2
–
4(3y
–
11)
+
y2
–
2y
–
5
=
0
 9y2
–
66y
+
121
–
12y
+
44
+
y2
–
2y
–
5
=
0
 10y2
–
80y
+
160
=
0
 y2
–
8y
+
16
=
0
 (y
–
4)2
=
0.
 The
two
possible
cutting
points
have
come
together
here
to
give
the
single
point
for
which
y
=
4
and

 x
=
12
–
11
=
1.
This
means
that
the
line
3y
=
x
+
11
just
touches
the
circle
–
it
is
a
tangent
to
it.
 The
point
of
contact
has
the
coordinates
(1,4).
 (c)
This
time,
we
put
y
=
3x
+
6
in
the
equation
of
the
circle.
This
gives
us
 x2
–
4x
+
(3x
+
6)2
–
2(3x
+
6)
–
5
=
0
 x2–
4x
+
9x2+
36x
+
36
–
6x
–
12
–
5
=
0
 10x2
+
26x
+
19
=
0.
 Using
the
quadratic
formula
on
this
equation,
with
a
=
10,
b
=
26
and
c
=
19
gives
b2
–
4ac
=
–84,
so
we
can’t


find
any
value
for
x
which
will
satisfy
this
equation.

 This
must
mean
that
the
line
misses
the
circle
completely.
 For
the
sketch,
we
need
the
centre
and
the
radius
of
the
circle.
 We
have
 x2–
4x
+
y2
–
2y
–
5
=
0
 (x
–
2)2
–
4
+
(y
–
1)2
–
1
–
5
=
0
 so
(x
–
2)2
+
(y
–
1)2
=
10.
 The
centre
of
the
circle
is
at
the
point
(2,1)
and
its
radius
is
 


10 



 
 Straight
lines
and
circles
 • Substituting
the
equation
of
the
line
into
the
equation
of
the
circle
will
give
you
a
quadratic
equation
 in
x
or
y.

 The
equation
has
two
roots.
This
means
that
the
line
cuts
the
circle
in
two
points.
 The
equation
has
one
repeated
root.
This
means
that
the
line
is
a
tangent
to
the
circle
–
it
just
 touches
it.
 ‘b2
–
4ac’
is
negative,
and
the
equation
has
no
real
roots.
This
means
that
the
line
misses
the
circle
 altogether.


There
are
then
three
possibilities.
 • • • 


Finding
the
equations
of
tangents
to
circles

Any
tangent
to
a
circle
must
be
perpendicular
to
the
radius
going
to
the
point
of
contact.
The
gradient
of
the
 tangent
will
then
tell
us
the
slope
or
gradient
of
the
circle
at
this
point
of
contact.
 
 Example
(1)
Find
the
equations
of
the
four
tangents
to
the
circle
x2
–
6x
+
y2
–
4y
–
12
=
0
with
points
of
 contact
(a)
(7,5),
(b)
(–1,
–1),
(c)
(8,2)
and
(d)
(3,7).
Draw
a
sketch
showing
the
circle
and
these
four
 tangents.
 
 Answer:

 We
start
by
finding
the
centre
and
radius
of
the
circle.

We
have
 x2
–
6x
+
y2
–
4y
–
12
=
0
=
(x
–
3)2
–
9
+
(y
–
2)2
–
4
–
12.
 So
the
equation
of
the
circle
is
also
given
by
(x
–
3)2
+
(y
–
2)2
=
25.
Its
centre
is
at
the
point
(3,2)
and
 its
radius
is
5
units.
I
have
drawn
a
sketch
of
this
circle
in
Figure
showing
the
first
tangent
that
we
 shall
find.
I
think
that
it
will
help
you
in
the
working,
which
follows
if
you
sketch
in
how
you
think
the


other
three
tangents
will
go.
 




 (a)
The
first
tangent
touches
the
circle
at
the
point
(7,5).
The
radius
to
the
point
of
contact
joins
(3,2)
to
 (7,5),
so
its
gradient
is



 


y2 - y1 5-2 3 x2 - x1 = 7 - 3 = 4 
 Demo